Sigmoid Volvulus in Pregnancy Assessed by Contrast-Enhanced Computed Tomography Scanning - Toshiaki Watanabe; Tadatsugu Kinjo; Yoshino Kinjyo; Hayase Nitta; Hitoshi Masamoto; Keiko Mekaru; Yoichi Aoki (Hindawi Limited, 2021)
Sigmoid volvulus requires urgent treatment, and it is particularly rare among pregnant women without a history of laparotomy. A delay in diagnosis may lead to serious consequences for the mother and fetus, and a rapid diagnosis and treatment in this setting is essential. The patient was a 19-year-old primiparous woman. She complained of repeated exacerbations and remissions of abrupt lower abdominal pain for the past 2 days and was transported to our hospital at 33 weeks of gestation. Ultrasonography revealed no placental thickening, and maternal bowel dilation was difficult to identify. Plain abdominal X-ray showed a dilated colon on the left side of the abdomen. Contrast-enhanced CT scan of the abdomen revealed a volvulus on the dorsal side of the uterus. The proximal end of the transverse to sigmoid colon was markedly dilated, and the distal end was collapsed. The elevated lactate level on blood gas analysis suggested intestinal ischemia. She was suspected of having a sigmoid volvulus at 33 weeks and 3 days of gestation. We decided to perform a cesarean section to secure the operative field for an intestinal resection following delivery. A male weighing 1840 g with Apgar scores 8/8 was delivered. The sigmoid colon was approximately 80 cm in length. A 360-degree clockwise rotation of was observed with a very distended but viable sigmoid loop. Following reduction of the volvulus, the sigmoid colon was fixed to the left side of the peritoneum. The mother had an uneventful postoperative course, and the infant was discharged without any sequelae. This case demonstrates two important lessons. First, sigmoid volvulus can occur in pregnant women even if they never had a laparotomy. Second, abdominal contrast-enhanced CT is useful for rapid diagnostic and treatment decisions relative to this pathology.